Barbie. Mariposa and her butterfly fairy friends - Universal Studios Home Entertainment (Firm) (Universal City, Calif. : Universal Studios Home Entertainment, 2008)
Mariposa is a beautiful butterfly fairy who loves to read and dream about the world outside her home in the land of Flutterfield. Flutterfield is protected by the Queen's glimmering magical flower lights. But when the Queen is poisoned by the evil fairy Henna, the special lights begin to go out one by one. It's up to the brave Mariposa and her friends to journey beyond the safe borders of the city in search of a hidden antidote that will save the Queen.
Title from container.
Special features: Flutterfield Scavenger Hunt; Flutterpixie Dress up.
Not rated.
DVD, region 1, anamorphic widescreen (1.78:1) presentation; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo., single-layer.
English (Dolby 5.1, Dolby 2.0), dubbed French (Dolby 2.0) or dubbed Spanish (Dolby 2.0) dialogue; English subtitles for the deaf and hard of hearing.
Keywords: Barbie (Fictitious character) -- Juvenile drama; Fairies -- Juvenile drama; Poisoning -- Juvenile drama; Antidotes -- Juvenile drama; Video recordings for the hearing impaired